Respuesta :

Answer:

x=2   and   y=1

Step-by-step explanation:

1). Plug the y value into the second equation. It will look like the following afte you plug in what y equals:

              -2x-3(6x-11)=-7

2). Then, you distribute the "-3" to all the terms inside the parenthesis.

              -2x-18x+33=7

3). Then, you subtract the positive 33 from both sides to try to get the x alone on one side.

              -2x-18x=-40

4.) Then, you combine all of the terms containing an x.

              -20x=-40

5). Finally, you divide both sides by -20 and the outcome is x=2.

6).  Hold up...we ain't done yet..

7).  Next, you have to plug the x back into the either equation to get the outcome of what y will be, but for this purpose I will plug it back into the first equation.

              y=6(2)-11

8). I will then distribute the 6 into the all the terms in the parenthesis and then it will look like this.

              y= 12-11

9). Do the math...and the answer is y=1.